Oxidative Cleavage of Aromatic Azines with Periodic Acid; MO Model for the Reaction Intermediate - Alexander J. Fatiadi (CHIMIA)
Cleavage of benzalazine (and other azines) with periodic acid may initially involve, as a single step, the addition of IO4- (or its hydrate) across the conjugated azine system, to give an iodate I (V) complex; this view is supported from MO symmetry rules.